Model of financial and economic results of the company in accordance with the concept of Six Sigma - Arych, Mykhailo (My University, 2016)
The paper identified key components of a management model financial and economic results of the company in accordance with the concept of Six Sigma. The model combines the existing controls and innovative components improve the management concept based on Six Sigma including planning, forecasting, performance management effectiveness evaluation, basic and trystupenevi management strategy, optimization and control.
Keywords: Six Sigma; costs; financial and economic performance; model management; модель управління; витрати; фінансово-економічні результати; расходы; финансово-экономические результаты; модель управления; кафедра фінансів